H01 Upcoming international guidelines in huntington's disease. (September 2018) - Massart, Renaud; Ferreira, Joaquim; Youssov, Katia; Rosser, Anne; Busse, Monica; Craufurd, David; Reilmann, Ralf; Michele, Giuseppe De; Rae, Daniela; Squitieri, Ferdinando; Seppi, Klaus; Burgunder, Jean-Marc; et al.
Abstract : Background: More than a century after the first description of Huntington's disease (HD), there is still no curative treatment of the disease; however, symptomatic treatments are thought to be efficacious in controlling some of its more troublesome symptoms. Yet, symptomatic management of HD remains inadequately documented, which may lead to variations in care mainly based on clinical experience and not on scientific evidence. Aims: The European Huntington's Disease Network (EHDN) commissioned an international working group to provide global evidenced based recommendations for everyday clinical practice for treatment of HD. The objectives of such guidelines are to standardize pharmacological, surgical and non-pharmacological treatments' regimen and improve care and quality of life of patients. Methods: A formalized consensus method, adapted from the French Health Authority recommendations (and aligned to the Grade system), was used. First, French and English Expert committees reviewed all evidence published between 1965 and 2015. Grades were determined based on levels of scientific evidence. When evidence was missing, recommendations were framed based on professional agreement. The initial recommendations were reviewed by a Steering Committee before initiating a consensus process with 60 international multidisciplinary HD health professionals. This involved two rounds of online questionnaire completion. After the 1st round, only recommendations with strong consensus were retained. Those without strong consensus were reviewed and modified by the Steering Committee prior to the second round of ranking. Conclusion: Two hundred and seventeen statements dealing with motor, cognitive, psychiatric and somatic disorders were retained in the final guidelines. Patients' associations are being consulted on readability of the recommendations prior to publication.